FRI0548 Physical and mental health in ra patients treated with biologic dmards - two-year follow-up data of the german biologics register rabbit. (23rd January 2014) - Gerhold, K.; Richter, A.; Schneider, M.; Bergerhausen, H. J.; Demary, W.; Liebhaber, A.; Zink, A.; Strangfeld, A.
Abstract : Background: Health-related quality of life (HRQoL) has been identified as a key indicator of disease burden in chronic diseases such as rheumatoid arthritis (RA). Objectives: To measure the effectiveness of biologic (b) versus non-biologic (nb) disease modifying anti-rheumatic drugs (DMARDs) on physical and mental health as two main dimensions of HRQoL in patients with RA. Methods: Patients enrolled in the German biologics register RABBIT between 2006 and 2011 with a minimal observation time of 12 months were included. HRQoL was captured by the patient-assessed mental and physical health scales of the SF-36 questionnaire at baseline, and at months 12 and 24 of follow-up. Propensity score matching was used to adjust for baseline differences between the groups. The score is based on the probability of receiving a biologic agent modeled by means of logistic regression. Adjustments were made for sex and the baseline variables disease duration, rheumatoid factor, number of previous DMARDs, disease activity (DAS28), functional ability (FFbH), joint erosions, and co-morbidities. We applied sequential regression modeling for multiple imputation of missing values. To take different observation periods between individuals of the ITT groups into account, the two-year course of HRQoL was predicted by multi-level modeling adjusted for sex and the baseline variables rheumatoid factor, disease duration, joint erosions, DAS28 and FFbH. Results: Data of 109 abatacept-treated patients, 1040 patients treated with TNF-α inhibitors, 461 rituximab-treated patients, 268 tocilizumab-treated patients, and of 254 patients treated with nbDMARDs were included in the analysis. At baseline all patients treated with bDMARDs had higher disease activity, and poorer values of all physical and mental health subscales than patients treated with nbDMARDs. Physical and, even more noticeable, mental health improved in all patients independently from therapy, particularly within the first 12 months. This improvement was superior in patients treated with bDMARDs compared to patients treated with nbDMARDs. Patients adhered to the level of improvement between months 12 and 24 (Table 1 ). Conclusions: In all treatment groups, patients' HRQoL improved beyond control of disease activity and physical function. Since patients maintained the level of improvement between months 12 and 24, the benefit in the two main dimensions of HRQoL, physical and mental health, can be considered as a sustainable effect of treatment. Disclosure of Interest: K. Gerhold Grant/research support from: AbbVie, Bristol-Myers-Squibb, MSD SHARP & DOHME, Pfizer, Roche, and UCB., A. Richter Grant/research support from: AbbVie, Bristol-Myers-Squibb, MSD SHARP & DOHME, Pfizer, Roche, and UCB., M. Schneider: None Declared, H. J. Bergerhausen: None Declared, W. Demary: None Declared, A. Liebhaber: None Declared, A. Zink Grant/research support from: AbbVie, Bristol-Myers-Squibb, MSD SHARP & DOHME, Pfizer, Roche, and UCB., A. Strangfeld Grant/research support from: AbbVie, Bristol-Myers-Squibb, MSD SHARP & DOHME, Pfizer, Roche, and UCB.